ASUHAN KEPERAWATAN PASIEN STROKE HEMORAGIK DALAM PEMENUHAN KEBUTUHAN FISIOLOGIS : OKSIGENASI - Ratna Eka Nur Ainy; Ari Pebru Nurlaily (Journal of Advanced Nursing and Health Sciences, 2021)
Hemorrhagic strokes occur due to the rupture of a blood vessel which causes blood in the brain to flow into the cavity around the brain tissue. Patients with hemorrhagic strokes will experience a decrease in consciousness because the need for oxygen and nutrients carried by the blood to the brain is not fulfilled due to the rupture of blood vessels. Awareness is a basic need that must be fulfilled for human survival. Patients with decreased consciousness need to be given a stimulus. One of the management of hemorrhagic stroke patients with decreased consciousness is Murottal Al-Qur'an therapy to increase the level of consciousness (GCS). The purpose of this case study was to determine the description of nursing care in hemorrhagic stroke patients in meeting their physiological needs (oxygenation). The study was conducted from 18 to 23 February 2020 in the HCU room at Salatiga Hospital. This type of study was descriptive with a case study approach. The subject was Mrs. M with a medical diagnosis of hemorrhagic stroke in meeting physiological needs. The result of nursing care management in hemorrhagic stroke patients in fulfilling physiological needs with nursing problems are the risk of ineffective cerebral perfusion by performing Murottal Al-Qur'an therapy for six consecutive days in 30 minutes/action presented an improvement in the consciousness level from the initial score of GCS 6 E2V1M3 (Sopor) becomes GCS 8 E3V1M4 (Somnolen). Recommendation: Murottal Al-Qur'an therapy is effective in hemorrhagic stroke patients with decreased consciousness.